Metagenomic insights into the dominant Fe(II) oxidizing Zetaproteobacteria from an iron mat at Lō´ihi, Hawai´l - Singer, Esther; Heidelberg, John F.; Dhillon, Ashita; Edwards, Katrina J. (Frontiers in Microbiology, 2013)
Zetaproteobacteria are among the most prevalent Fe(II)-oxidizing bacteria (FeOB) at deep-sea hydrothermal vents; however, knowledge about their environmental significance is limited. We provide metagenomic insights into an iron mat at the Lō´ihi Seamount, Hawai´l, revealing novel genomic information of locally dominant Zetaproteobacteria lineages. These lineages were previously estimated to account for 13% of all local Zetaproteobacteria based on 16S clone library data. Biogeochemically relevant genes include nitrite reductases, which were previously not identified in Zetaproteobacteria, sulfide:quinone oxidases, and ribulose-1,5-bisphosphate carboxylase (RuBisCo). Genes assumed to be involved in Fe(II) oxidation correlate in synteny and share 87% amino acid similarity with those previously identified in the related ZetaproteobacteriumMariprofundus ferrooxydans PV-1. Overall, Zetaproteobacteria genes appear to originate primarily from within the Proteobacteria and the Fe(II)-oxidizing Leptospirillum spp. and are predicted to facilitate adaptation to a deep-sea hydrothermal vent environment in addition to microaerophilic Fe(II) and H2S oxidation. This dataset represents the first metagenomic study of FeOB from an iron oxide mat at a deep-sea hydrothermal habitat.